EFFICIENCY OF LARGE-SIZED MYSTUS KELETIUS (VALEN) IN EXTRACTING DISSOLVED OXYGEN FROM LOW PARTIAL PRESSURE - Santhanakumar, G; Job, S V; Vinojlal, S (Indian Journal of Fisheries, 2011)
Literature pertaining to partial pressure of dissolved oxygen (p02)temperature etc., are too scanty (Basu 1959, Beamish 1964, Fry 1947 and1957, Job 1955 and 1957). In Tambaraparani river system, temperture rangesbetween 23 ± 1°C and 29 ± 1°C. The dissolved oxygen was found to bevarying from 7.6 mg/1 to 2.5 mg/1 both in the surface and bottom (wheredepth is less than a meter), respectively.